Voxel-Wise Quantitative Mapping of the Brain Association Ability - Chen, Kai; Wang, Lijie; Zeng, Jianguang; Chen, Ai; Gao, Zhao; Wang, Jiaojian (Frontiers in Neuroscience, 2021)
The association cortices of the brain are essential for integrating multimodal information that subserves complex and high-order cognitive functions. To delineate the changing pattern of associative cortices can provide critical insight into brain development, aging, plasticity, and disease-triggered functional abnormalities. However, how to quantitatively characterize the association capability of the brain is elusive. Here, we developed a new method of association index (Asoo) at the voxel level to quantitatively characterize the brain association ability. Using the Asoo method, we found high Asoo values in association cortical networks while low values in visual and limbic networks, suggesting a pattern of significant gradient distribution in neural functions. The spatial distribution patterns of Asoo show high similarities across different thresholds suggesting that Asoo mapping is a threshold-free method. In addition, compared to functional connectivity strength, i.e., degree centrality method, Asoo mapping showed different patterns for association cortices and primary cortices. Finally, the Asoo method was applied to investigate aging effects and identified similar findings with previous studies. All these results indicated that Asoo can characterize the brain association patterns effectively and open a new avenue to reveal a neural basis for development, aging, and brain disorders.